A Yank in the R.A.F. [videorecording (DVD)] - Power, Tyrone, 1914-1958; Grable, Betty, 1916-1973; Ware, Darrell, 1906-1944; King, Henry, 1886-1982 (Fox war classics., 2002)
A cocky American flier joins the RAF to be near the woman he loves, a London-based singer.